2019
DOI: 10.5530/ijpi.2019.3.21
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative and Qualitative Assessment of Aegle marmelos Global Publications during 2004-18

Abstract: The present study examined 962 global publications on Aegle marmelos, as covered in Scopus database during 2004-18, with a view to understand its growth rate, global share, citation impact, international collaborative papers share, distribution of publications by broad subjects, productivity and citation profile of top organizations and authors, preferred communication media and characteristics of high cited papers. Aegle marmelos global output registered 36.37% annual growth and averaged 16.0 citations per pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The names of important organizations, researchers and companies were also identified. Similar bibliometric studies have been carried out on other medicinal plants, such as Aegle marmelos, 9 Aloe vera, 10 Andrographis paniculata, 11 Azadrachta indica, 12 Curcuma longa, 13 Glycyrrhiza glabre, 14 Nigella sativa, 15 Ocimum sanctum, 16 Phyllanthis emblica, 17 Rhodiola rosea, 18 Tinospora cordifolia 19 and Withania somnifera. 20 Since India is the largest contributor to global Moringa oleifera research and as yet no bibliometric study has been published on the bibliometric assessment of India's research in this area, as a result we felt the need to undertake the present study.…”
Section: Literature Reviewmentioning
confidence: 56%
“…The names of important organizations, researchers and companies were also identified. Similar bibliometric studies have been carried out on other medicinal plants, such as Aegle marmelos, 9 Aloe vera, 10 Andrographis paniculata, 11 Azadrachta indica, 12 Curcuma longa, 13 Glycyrrhiza glabre, 14 Nigella sativa, 15 Ocimum sanctum, 16 Phyllanthis emblica, 17 Rhodiola rosea, 18 Tinospora cordifolia 19 and Withania somnifera. 20 Since India is the largest contributor to global Moringa oleifera research and as yet no bibliometric study has been published on the bibliometric assessment of India's research in this area, as a result we felt the need to undertake the present study.…”
Section: Literature Reviewmentioning
confidence: 56%
“…Many researchers have also explored studies relevant to medicinal plants. [3][4][5][6][7][8][9][10][11][12][13][14] This study identified India's contribution in international collaboration documents at the national level and key partners in international collaboration, further analyzing the characteristics of institutions, authors, frequently cited articles, etc.…”
Section: Related Studiesmentioning
confidence: 99%